Use as a puppet punakawan media co (strengthening of character education) to increase awareness of culture class IX B SMP Negeri 3 pamotan - Eka Wahyuningsih (Ikatan Bimbingan dan Konseling Sekolah)
This study aims to determine the effect of the use of puppets as a medium Punakawan PPK (Strengthening the Character Education) towards the increase of cultural awareness of IXB students of SMP Negeri 3 Pamotan. This research uses experimental research approach (quantitative) with the kind of one-group pretest-posttest design in the use of puppets as a medium Punakawan PPK (Strengthening the Character Education). The subjects of this study are 8 students who have low cultural awareness. Analyze this data using non parametik statistic by using sign test. The results of the data analysis shows that ρ = 0.004 showed smaller compared with α = 0, 5. Thus H a received and H 0 is rejected, so there is a difference in students' cultural awareness between before and after treatment, it can be concluded that the use of puppets as a medium Punakawan PPK (Strengthening the Character Education) can increase the cultural awareness of students of IXB class SMP Neg